2005
DOI: 10.1080/03079450400025414
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the spike protein of the 793/B type of infectious bronchitis virus, in the field and during alternate passage in chickens and embryonated eggs

Abstract: The degree of variation exhibited within the 793/B serotype (also known as 4/91 and CR88 serotypes) was investigated with nine French and 10 British isolates, collected between 1985 and 1994. The S1 part (1644 nucleotides) of the spike protein gene of the first known isolate of this serotype, FR/CR85131/85, had 95.9% to 97% nucleotide identity with the other isolates. Partial sequencing of isolates from Iran and Saudi Arabia, isolated in 2000, revealed approximately 95% nucleotide identity with European isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
88
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 33 publications
7
88
1
Order By: Relevance
“…These results are in concurrence with previous in vivo work, which demonstrated that the majority of nucleotide variations in 793B were synonymous (Cavanagh et al, 2005). However, in the presence of Mass (Group C), there was a marked increase in 793B SNPs per 100 bp (particularly at 4 days p.i., 0.55 per 100 bp in the dual compared with 0.03 in the single vaccinations), with the majority now causing a change in the amino acid composition.…”
supporting
confidence: 92%
“…These results are in concurrence with previous in vivo work, which demonstrated that the majority of nucleotide variations in 793B were synonymous (Cavanagh et al, 2005). However, in the presence of Mass (Group C), there was a marked increase in 793B SNPs per 100 bp (particularly at 4 days p.i., 0.55 per 100 bp in the dual compared with 0.03 in the single vaccinations), with the majority now causing a change in the amino acid composition.…”
supporting
confidence: 92%
“…Vaccination programmes against IB must be based on the identification of the IBV strains causing the disease in the field (Hofstad, 1981) because nucleotide differences between isolates in S1 sequences are sufficient to change the serotype, and there is poor cross-protection between them (Cavanagh & Naqi, 2003;Cavanagh et al, 2005). Therefore, identification is important for the selection of the most appropriate vaccine to control the outbreak (Farsang et al, 2002).…”
mentioning
confidence: 99%
“…Since it was first described in the early nineties in United Kingdam, 4/91 type IBVs was identified in many other countries and became one of the most predominant genotype in Europe [4,6]. Almost all IBVs recently isolated in Japan have been classified into three major genotypes, JP-I, JP-II and JP-III, but isolates of the 4/91 genotype have been sporadically detected since 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Cavanagh et al [4] examined passage of the 4/91 vaccine strain in chickens, compared the S1 sequences of vaccine strains and examined the pathogenicity of egg-passaged and chick-passaged strains. In their report, they recognized one amino acid substitution at position 95, alanine in the vaccine strain and serine (S) in the chick-passaged strain, in the strain after 10 passages in the chicken, but the pathogenicity of the chick-passaged strain did not change.…”
Section: Discussionmentioning
confidence: 99%